2013
DOI: 10.3390/s130607505
|View full text |Cite
|
Sign up to set email alerts
|

Early Improper Motion Detection in Golf Swings Using Wearable Motion Sensors: The First Approach

Abstract: This paper presents an analysis of a golf swing to detect improper motion in the early phase of the swing. Led by the desire to achieve a consistent shot outcome, a particular golfer would (in multiple trials) prefer to perform completely identical golf swings. In reality, some deviations from the desired motion are always present due to the comprehensive nature of the swing motion. Swing motion deviations that are not detrimental to performance are acceptable. This analysis is conducted using a golfer's leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
(13 reference statements)
0
24
0
1
Order By: Relevance
“…In the surgical field, skilled surgeons can perform surgical procedures with a significant economy of movement (on real and simulated procedures), if compared to the number of movements (much higher) required by a resident [73,83,84]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the surgical field, skilled surgeons can perform surgical procedures with a significant economy of movement (on real and simulated procedures), if compared to the number of movements (much higher) required by a resident [73,83,84]. …”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the magnitude of angular speed (Sω) was calculated from the X, Y and Z gyroscopic signals using Equation (1):Sω=ωx2+ωy2+ωz22 Sω signal was used to discriminate individual hand movements, as it was observed that peaks on Sω signal occurs each time the hand movement changes (e.g., a change between Task_1 and Task_2) [73]. Therefore, those peaks were used to segment the movements in epochs.…”
Section: Methodsmentioning
confidence: 99%
“…Due to integration, the error in the computed angular orientation accumulates over time. To make the results comparable across different simulations and measurements, we normalize the deviation angle ε (14) with respect to the total time of rotation T:…”
Section: Angular Orientation Systematic Errormentioning
confidence: 99%
“…With the ongoing developments in gyroscope-manufacturing technology, their use in various fields is observably increasing . 3D gyroscopes are integral components of inertial navigation units [5][6][7][8]; have been shown feasible for motion capture, classification, and analysis [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]; and are essential elements of the assistive, rehabilitative, and wearable health technology [21,22]. However, the utility of 3D gyroscopes can be diminished without an associated meaningful interpretation of the measured values and computation of the angular orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The devices obtain an individual golfer's values during the swing, which are analyzed by many researchers. (6,(14)(15)(16) In contrast, noncontact sensing uses pictures or videos to record a golfer's actions during the swing, and the actions are analyzed.…”
Section: Motion Analysis Of Golf Swingmentioning
confidence: 99%